Діалектні картини Італії та України: спроби порівняння - Дель Гаудіо, С. (Мовознавство, 2018)
Стаття присвячена систематизації основних засад італійської діалектної класифікації. Уперше в межах контрастивних студій зроблено спробу порівняти італійську діалектну картину з українською, що має на меті сприяння розвитку подальших досліджень як італійсько-українських, так і романсько-слов’янських діалектів
узагалі. Classifications of Italian and Ukrainian dialects are rather numerous in the respective
dialectal / linguistic traditions. Yet Ukrainian outlines of Italian dialects are both limited
in number and tendentially inexact. At the same time Italian descriptions of Ukrainian
dialects, with very few exceptions, are basically inexistent in Italy. For this reason in this
paper we made an attempt at presenting a first comparative taxonomy of both Italian and
Ukrainian dialects, e. g. basic classification and subdivision criteria. The underlying aim
of this contribution intends to increase the further development of Italian-Ukrainian and,
more at large, Romance-Slavic comparative dialectal studies.